266 CORRELATES OF READINESS TO CHANGE DRINKING BEHAVIORS AMONG A SAMPLE OF INNER-CITY EMERGENCY DEPARTMENT PATIENTS WITH AN ALCOHOL PROBLEM. Issue 1 (1st January 2007) - Antelo, F.; Bazargan-Hejazi, S.; Ani, C.
Abstract : The high rate of alcohol use among emergency department (ED) patients makes the ED setting an obvious target for increased screening and interventions. However, interventions to change alcohol behavior may be applied inappropriately if a patient's motivation to change is not factored in. Purpose of the Study: To identify correlates of readiness to change problem drinking among a sample of ED patients. Method: This study analyzes secondary data obtained from an earlier ED study conducted at the King/Drew Medical Center between August 2001 and December 2001 (9 am to 6 pm, 5 days a week). This study used a sample of 295 ED patients who scored positive for an alcohol problem based on CAGE (score ≥ 1). Results: 68% African American; 32% Latino; 80% male; 46% less than high school diploma; 85% not married; 72% no health insurance; 85% no primary care health provider. Whereas 12% of the patients were "not ready" to change their drinking behaviors, 47% and 41% were "unsure" and "ready, " respectively. Using multiple regression analysis revealed that among a list of four potential predictors (illicit drug use, tobacco use, exposure to violence, and having a primary care doctor), and six controlling variables (gender, ethnicity, education, marital status, insurance, ability to afford medication), reporting use of illicit drug(s), reporting exposure to violence, being female, and being married contributed significantly to the likelihood of changing one's level of readiness to change alcohol behaviors ( p ≤ .05). Conclusion: Recognizing ED patients' level of motivation to change problem drinking and factors that move one toward a higher level of readiness can help researchers improve the receptiveness and effectiveness of alcohol behavior interventions.